THE USE OF THE STORYTELLING METHOD IN THE MATERIAL OF TELLING THE CONTENT OF FAIRY TALES FOR GRADE III STUDENTS OF UPTD SD NEGERI 3 PEULIMBANG, BIREUEN REGENCY - Atika, Zuhra; Idham, Muhammad; Safiah, Intan (Elementary Education Research, 2025)
The objectives of this research are as follows. Describe the use of the storytelling method in material telling the content of fairy tales for class III students at UPTD SD Negeri 3 Peulimbang, Bireuen Regency. Describe students' speaking abilities in the material for telling the content of fairy tales using the storytelling method for class III students at UPTD SD Negeri 3 Peulimbang, Bireuen Regency. Describe the students' ability to find the message of the story. fairy tales using the storytelling method for class III UPTD students at SD Negeri 3 Peulimbang, Bireuen Regency. using a qualitative approach with a descriptive research type, the research site is SD Negeri 3 Peulimbang with a class III population of 21 people, data collection techniques using performance tests, and percentage data analysis techniques. From the data obtained, it is known that from the 25 students who took the test, 19 students were declared capable tell and find the moral message of the fairy tale by successfully getting a score of or equal to the minimum completeness criteria (KKM) score for Indonesian language subjects, namely 68, if it is a percentage, the number of students who are able to tell and find the moral message of the fairy tale is 90.4% ( 19/21 X 100%). Meanwhile, 2 other students were declared unable or still having difficulty in telling and finding the moral message of fairy tales, if the percentage was 9.6% (2/21 X 100%). From this percentage, it can be said to have achieved the expected speaking ability criteria. Students who are unable to do so are students who still find it difficult to tell and find the moral message of fairy tales. Thus, remediation needs to be carried out for students who are unable to do so. Based on the criteria that have been determined, if 85% of students are capable in the test, then learning is said to be successful. Thus, it can be concluded that learning through the storytelling method on the material of telling the content of fairy tales at SD Negeri 3 Peulimbang, Bireuen Regency can achieve completeness, because 90.4% of students are able to tell and find the moral message of fairy tales or reach the minimum completeness criteria (KKM) score. namely 68. Based on data analysis, if 85% of students are capable in the test, then learning is said to be successful. Thus, it can be concluded that learning through the storytelling method on the material of telling the content of fairy tales at UPTD SD Negeri 3 Peulimbang, Bireuen Regency can achieve completeness, because 90.4% of students are able to tell and find the moral message of fairy tales or achieve the minimum completeness criteria (KKM) score. ) which is 68.